An exploration into the drivers of social media usage among MSME handicraft entrepreneurs / Susana William Jalil ... [et al.] - Jalil, Susana William; Haris, Nurfazlina; Putit, Lennora; Awang Shuib, Awang Rozaimie (Faculty of Business and Management, 2022)
Being an essential component of Micro, Small, and Medium Enterprises (MSMEs), the emergence of social media in marketing is critical in attempting to make handicraft product businesses more financially viable. This study aims to explore the adoption of social media marketing by MSME handicraft entrepreneurs in the state of Sarawak, Malaysia. Using a purposive sampling technique, qualitative data were collected from 15 participants comprising MSME handicraft entrepreneurs via indepth interviews. Data were transcribed and analysed using NVIVO 12.0 software. Findings revealed the following identification of themes: performance, effort expectancy, social relationship quality, social influence, and facilitating conditions. Further discussions were subsequently deliberated.